Assessment of the Persistent Organic Compounds Residual Level of Telfaria occidentalis Hook F. Leaves (Ugu) Cultivated in the Federal Capital Territory, Abuja - Nigeria - , Nnrani F. I.; , Ogunlade-Anibasa G. O.; , Ndana R. W.; , Aliyu H. D. (Archives of Current Research International, 2025)
This study investigated persistent organic compounds residue level in Telfaria occidentalis Hook F. Leaves (Ugu) cultivated in the Federal Capital Territory, Abuja Nigeria. T. occidentalis was collected from 12 farms, 2 each per Area Council using a circular grid of 20m apart. Random sampling technique was used to collect samples T. occidentalis (Ugu) leaves at six different spots within the farm to form composite sample during the rainy season (August, 2023). The POCs residue levels were determined using Gas Chromatography-Electron Capture Detector (GC-ECD). Alpha-BHC, Beta-BHC, Gamma-BHC, Aldrin, Heptachlor, Endrin, DDT (Dichlorodiphenyltrichloroethane) and Endosulfan Sulfate were recorded in T. occidentalis across the Area Councils of all these, Heptachlor has the highest concentration of 15.67mg/kg, followed by Endrin with 15.25mg/kg, Beta – BHC with 13.87mg/kg, Endosulfan Sulfate with 8.56mg/kg, DDT with 7.49mg/kg, Alpha – BHC with 4.86mg/kg, Aldrin with 2.17mg/kg and the lowest concentration is that of Gamma – BHC with o.49mg/kg. Occurrence of these POCs was also ranked across the Area Councils where some Area Council ranked first in some POC and closely followed by others an indication of indiscriminate use of pesticides in these Area Councils particularly those detected for which the Area Councils ranked first. There was no significant difference (p˂0.05) in the concentrations across the six Area Councils. However, these concentrations been above Maximum Residue Limits (MRLs) permissible by the World Health Organization/ Food and Agricultural Organization (WHO/FAO ) and National Environmental standard and Regulations Enforcement Agency (NESREA) which implies that there is a potential health risk for human and animals that consume these vegetables however, the extent of health effects will depend on the quantity and frequency of consumption and this calls for strict regulation of the application of the pesticides in farms.